2020
DOI: 10.2478/udi-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Geography of research on post-socialist cities: a bibliometric approach

Abstract: The main aim of the article is to investigate the spatial structure of international research on post-socialist cities. The analysis is based on data derived from the Scopus database (2001–2018) and includes issues such as the publication dynamics, structure of authors (with regard to cities and countries), main publishing ‘channels’, as well as networks in ‘producing’ knowledge on post-socialist cities. The analyses conducted primarily lead to a general conclusion about the high spatial concentration of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…With the passage of time since the collapse of the Eastern Bloc, the influence of post-socialist factors on the current state of urban affairs in Central and Eastern Europe (CEE) seems to be waning (Bajerski, 2020). However, it is debatable what is to be understood as post-socialist, whether the phenomena associated with the state socialist past are actually linked to it, and how strong this relationship is (Müller, 2019;Tuvikene, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…With the passage of time since the collapse of the Eastern Bloc, the influence of post-socialist factors on the current state of urban affairs in Central and Eastern Europe (CEE) seems to be waning (Bajerski, 2020). However, it is debatable what is to be understood as post-socialist, whether the phenomena associated with the state socialist past are actually linked to it, and how strong this relationship is (Müller, 2019;Tuvikene, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They noted a paucity of comparative studies. Bajerski (2020), investigating which countries and institutions have been contributing to the study of postsocialist cities, found a dominance of research from countries in Central and Eastern Europe (CEE), but his coverage identified an increasing number of articles on China and a notable absence of Russian institutions among the top 20 research institutions publishing on the topic (Bajerski, 2020). The above is indicative that there is a need for comparative studies of shrinking cities that include a broad range of postsocialist countries to identify commonalities, differences, and policy experiences.…”
Section: Introductionmentioning
confidence: 99%